PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA TOKO SERIOUS STORE PARUNG - Submission JORAPI; Muhamad Rizki Ananda; Ivantan (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the effect of product quality and price on customer satisfaction at Serious Store Parung, both partially and simultaneously. The method used is quantitative. The sampling technique used purposive sampling, which had direct experience and the sample in this study amounted to 96 respondents.. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of this research are that product quality influences customer satisfaction with the regression equation Y = 26,197 + 0.311 X1. Hypothesis testing obtained a calculated t value > t table or (3,354 > 1,986), this was also strengthened by the sig value. < sig. 0.050 or (0.001 < 0.050). Thus, Ho1 is rejected and Ha1 is accepted, meaning that partially there is a positive and significant influence between Product Quality and Customer Satisfaction. Price influences Customer Satisfaction with the equation Y = 4,364 + 0.892 X2. Hypothesis testing obtained a calculated t value > t table or (10,874 > 1,986), this was strengthened by the sig value. < sig. 0.050 or (0.000 < 0.050). Thus, Ho2 is rejected and Ha2 is accepted, meaning that partially there is a positive and significant influence between Price and Customer Satisfaction. Product Quality and Price influence Customer Satisfaction with the regression equation Y = 0.078 + 0.165 X1 + 0.840 X2. Hypothesis testing obtained a calculated F value > F table or (65,596 > 3.094), this was strengthened by the sig value. < sig. 0.050 or (0.000 < 0.050). Thus, Ho3 is rejected and Ha3 is accepted, meaning that simultaneously there is a positive and significant influence between Product Quality and Price on Customer Satisfaction at Serious Store Parung.